2018
DOI: 10.1158/2159-8290.cd-17-1124
|View full text |Cite
|
Sign up to set email alerts
|

YAP Is Essential for Treg-Mediated Suppression of Antitumor Immunity

Abstract: Regulatory T cells (Treg) are critical for maintaining self-tolerance and immune homeostasis, but their suppressive function can impede effective antitumor immune responses. FOXP3 is a transcription factor expressed in Tregs that is required for their function. However, the pathways and microenvironmental cues governing FOXP3 expression and Treg function are not completely understood. Herein, we report that YAP, a coactivator of the Hippo pathway, is highly expressed in Tregs and bolsters FOXP3 expression and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
157
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(176 citation statements)
references
References 47 publications
7
157
2
Order By: Relevance
“…Current cancer immunotherapy goals include reprogramming of myeloidderived suppressor cells (MDSCs), reactivation or expansion of cytotoxic CD8 cells, and inactivation or reduction of suppressive T regulatory (Treg) cells. Studies have shown that YAP promotes growth and proliferation of cancer cells, and more recently that it also enhances differentiation of the immunosuppressive T regulatory (Treg) subset of CD4+ cells (5,8,10,(12)(13)(14). Here, we report that YAP also plays an immunoinhibitory role in CD8 T cells, especially activated cytotoxic cells usually found in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Current cancer immunotherapy goals include reprogramming of myeloidderived suppressor cells (MDSCs), reactivation or expansion of cytotoxic CD8 cells, and inactivation or reduction of suppressive T regulatory (Treg) cells. Studies have shown that YAP promotes growth and proliferation of cancer cells, and more recently that it also enhances differentiation of the immunosuppressive T regulatory (Treg) subset of CD4+ cells (5,8,10,(12)(13)(14). Here, we report that YAP also plays an immunoinhibitory role in CD8 T cells, especially activated cytotoxic cells usually found in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 75%
“…Generally, YAP and TAZ are thought of as oncogenes whose hyperactivity enhances cell survival and proliferation of tumor cells. However, as more is becoming known about the Hippo pathway, non-canonical roles of its components are being discovered in immune cells that play a role in the tumor progression (13)(14)(15)(16)(17). The tumor environment has many hallmarks that include genome instability, angiogenesis, replicative immortality, and evasion of destruction by the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…The Hippo pathway has been implicated in coupling CD8 + T cell clonal expansion to terminal differentiation through upregulation of kinase LATS1 and Yap degradation (Thaventhiran et al, 2012). Yap has also been shown to be important for Treg function, as have the Hippo pathway kinases MST1 and MST2 (Du et al, 2014;Li et al, 2015;Ni et al, 2018;Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding microenvironmental mechanosensing has offered revolutionary leaps in the fields of cellular development, organ size regulation, stem cell differentiation, cancer metastasis, cellular senescence, and programmed cell death [13][14][15][16] . Recent works have established a role for YAP in immunity, but there have been no links yet between YAP and mechanics in immune cells [17][18][19][20] , and environmental mechanosensing has never been demonstrated for T cells.To understand the impact of forces at the tissue scale, we studied lymph nodes (LNs) during infection. Activated LN become stiff and swollen during an immune response, but shrink and return to a baseline of mechanical softness upon resolution.…”
mentioning
confidence: 99%